2020
DOI: 10.54055/ejtr.v24i.407
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Motivations and Experiences of Tourists Visiting the Gallipoli Peninsula as a Dark Tourism Destination

Abstract: The present study strives to understand the travel motivations and experiences of both domestic and international travellers visiting the Gallipoli Peninsula. Qualitative research methodology was utilized for this study, with a case study approach employed for the qualitative research design. Data were gathered using face-to-face interviews (n=44), participant observation and document analysis, and an inductive content analysis was then used to analyse the data. The research findings revealed that travellers v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 110 publications
(176 reference statements)
2
12
0
Order By: Relevance
“…Despite richness of the dark tourism literature, previous research relies on either qualitative (Çakar, 2020; Light and Ivanova, 2021; Podoshen et al , 2018) or quantitative data (Kang et al , 2018; Sharma and Nayak, 2019). The current study makes methodological contributions to the dark tourism literature by using mixed methods with exploratory sequential design.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite richness of the dark tourism literature, previous research relies on either qualitative (Çakar, 2020; Light and Ivanova, 2021; Podoshen et al , 2018) or quantitative data (Kang et al , 2018; Sharma and Nayak, 2019). The current study makes methodological contributions to the dark tourism literature by using mixed methods with exploratory sequential design.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…As such, thanatourism and tragedy-related tourism are interchangeably used to refer to dark tourism (Light, 2017). Some studies explore various motivations for dark tourism (Çakar, 2020; Ivanova and Light, 2018; Qian et al , 2021). Such motivations include reinforcing learning, building political or national identity and seeking novelty and remembrance (Kim and Thapa, 2018; Yan et al , 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to that, research has shown that involvement plays a moderating role in the connection between tourist motivation and TRI (San Martin, Collado, & Rodriguez del Bosque, 2013). Furthermore, scholars examined TI to visit the DTD of historical significance, influence of media, CS of thrill and morbid experience generates the TRI (Niemela, 2010;Blom, 2000;Cakar, 2020). Therefore, we hypothesise the following:…”
Section: Moderating Effect Of Tourist Involvement (Ti) In Dark Tourismmentioning
confidence: 97%
“…As already discussed in the literature review, the influence of DTMF may lead to TRI in DTD, this section will discuss the dimensions thereof. The literature tends to define understanding history (UH), MSM and CS as dimensions of DTMF (Cakar, 2020;Zheng et al, 2018;Lewis, Schrier, & Xu, 2021). The first dimension of the DTMF is UH.…”
Section: Influence Of Dark Tourism Motivational Factors Dimensions On...mentioning
confidence: 99%